Pola Perjalanan Wisata Kuliner Kota Medan - Dina Yunita (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2023)
Culinary tourism has a big part for developed a region, that is to develop the authentic food from the region. Therefore, it is necessary to create a travel pattern that could introduce the authentic of the culinary tourism in the region, especially culinary tourism in Medan city. This research aims to determine the culinary tour routes in Medan city and the estimated of distance and time to head to the culinary tourism in Medan city. This research used qualitative descriptive method by using interviews, literature study and documentation study. The results of this research indicate that, the culinary travel routes in Medan city is base site pattern and the estimated of distance and travel time are 6 kilometers and 10 minutes.